Influence of radiographic examination findings on recommendations made during routine clinical re‐evaluation of dogs with uncomplicated tibial plateau leveling osteotomy. Issue 1 (21st October 2020) - Alexander, Akash; Compagnone, Krizia; Grierson, James; Keeley, Benjamin; Kilduff‐Taylor, Andrea; Maskell, Kirsty; Moriera, Luis; Roch, Simon; Barnes, Darren; Campmany, Maria Del Mar; Bovis, Maria Del Mar; Alexander, Saji Daniel; et al.
Abstract: Objective: To determine the influence of follow‐up radiographic examination on recommendations made during routine clinical re‐evaluation of dogs that had undergone uncomplicated tibial plateau leveling osteotomy (TPLO). Study design: Retrospective multi‐institutional case series. Animals: Client‐owned dogs (N = 1010) that underwent uncomplicated TPLO. Methods: Records from 11 institutions were searched for dogs that had been treated with unilateral TPLO and had no history of postoperative complications before their routine follow‐up examination. The frequency of change in further clinical recommendations resulting from client‐ or clinician‐voiced concerns or radiographic abnormalities was investigated. Results: Follow‐up evaluation was performed at a median of 6 (range, 4‐15) weeks after TPLO. Radiographic examination findings contributed to a change in recommendations in 4.15% (38/915) of dogs presented without client concerns and without abnormalities at orthopedic examination. Abnormal radiographic findings alone influenced the management of 3.76% (38/1010) of dogs. An association was detected between clinical features and radiological findings leading to a change in recommendations ( P  < .0001). Administration of analgesia at the time of follow‐up was associated with radiographic abnormalities ( P = .017) and change in postoperative plans ( P = .0007). Conclusion: Radiographic examination findings at follow‐up did not influence the management of most dogs with uncomplicated TPLO. Clinical significance: Radiographic examination findings are unlikely to influence the treatment of dogs that seem to be recovering uneventfully from an uncomplicated TPLO without concerns from clients, analgesia, or abnormal findings on thorough orthopedic examination by a surgical specialist, at the time of the planned clinical re‐evaluation.